Permanent Densification of Calcium Aluminophosphate Glasses - Kapoor, Saurabh; Youngman, Randall E.; Ma, Lina; Lönnroth, Nadja; Rzoska, Sylwester J.; Bockowski, Michal; Jensen, Lars R.; Bauchy, Mathieu; Smedskjaer, Morten M. (Frontiers in Materials, 2019)
High temperature densification of oxide glasses influences their interatomic distances and bonding patterns, resulting in changes in the mechanical and chemical properties. Most of the high-pressure investigations have focused on aluminosilicate and aluminoborosilicate based glasses, due to their relevance for the glass industry as well as the geological sciences. Relatively few studies have explored the pressure-induced changes in structure and properties of phosphate based glasses, although P2O5 is an important component in various multicomponent oxide glasses of industrial interest. In this work, we investigate the influence of permanent densification on the structure, mechanical properties (Vickers’s hardness), and chemical durability (weight loss in water) of binary CaO-P2O5 and ternary CaO-Al2O3-P2O5 glasses. The densification of bulk glasses is obtained through isostatic compression (1-2 GPa) at the glass transition temperature. The binary CaO-P2O5 series is prepared with varying [CaO]/[P2O5] ratio to obtain glasses with different O/P ratios, while the ternary series CaO-Al2O3-P2O5 is prepared with constant O/P ratio of 3 (metaphosphate) but with varying [CaO]/([CaO]+[Al2O3]) ratio from 0 1. Using Raman and 31P NMR spectroscopy, we observed minor, yet systematic and composition-dependent changes in the phosphate network connectivity upon compression. On the other hand, 27Al NMR analysis of the compressed CaO-Al2O3-P2O5 glasses highlights an increase in the Al coordination number. We discuss these structural changes in relation to the pressure-induced increase in density, Vickers’s hardness, and chemical durability.